Private World(s): Gender and Informal Learning of Adults (Research on the Education and Learning of Adults, 2015)
This book is the third production from the ESREA Gender network and, once more, an opportunity to let the readers discover, or to know more, for a better understanding of questions related to gender and adult learning. It shows how researchers can be deeply involved in this specific field of adult education. The notion of informal learning has already been treated as a chapter in the 2003s book, but it becomes central and relevant in this new book considering the growing complexity of our society. Readership: Educational Researchers and their students